Circulating DNA changes are predictive of disease progression after transarterial chemoembolization. Issue 3 (1st November 2021) - Sefrioui, David; Verdier, Vincent; Savoye‐Collet, Céline; Beaussire, Ludivine; Ghomadi, Slim; Gangloff, Alice; Goria, Odile; Riachi, Ghassan; Montialoux, Hélène; Schwarz, Lilian; Tuech, Jean‐Jacques; Frebourg, Thierry; et al.
Abstract: Transarterial chemoembolization (TACE) is used to treat patients with unresectable hepatocellular carcinoma (HCC). We evaluated the clinical impact of a‐fetoprotein (AFP) and circulating cell‐free and tumor DNA (cfDNA and ctDNA) changes around the TACE procedure. Our prospective monocentric study enrolled consecutive patients treated with TACE, with samples collected at baseline (D − 1), Day 2 (D + 2) and 1 month (M + 1) after TACE. cfDNA was quantified by the fluorometric method, and ctDNA was quantified by digital polymerase chain reaction designed for two hotspot TERT mutations. Computerized tomography scans or magnetic resonance imaging were performed at M + 1 every 3 months following TACE and independently reviewed. The objective was to identify thresholds of cfDNA, ctDNA and AFP changes associated with progressive disease (PD) using receiver operating characteristic curves. Thirty‐eight patients were included from March 2018 to March 2019. All markers significantly increased from D − 1 to D + 2 ( P  < .005), and cfDNA and ctDNA significantly decreased from D + 2 to M + 1 ( P  < .0001). The analysis of changes from D − 1 to M + 1 identified thresholds at +31.4% for cfDNA and 0% for ctDNA that were significantly associated with PD at M + 1 (44.4% [>+31.4%] vs 3.8% [≤+31.4%] and 50.0% [>0%] vs 5.0% [≤0%], respectively). No significant threshold was identified for AFP. Using a score combining cfDNA and ctDNA, the patients were classified into high‐ or low‐risk PD groups at M + 1, with PD rates of 80.0% vs 4.3% ( P  = .001) and median progression‐free survival times of 1.3 vs 10.3 months ( P  = .002). Our study suggests that cfDNA and ctDNA increases around the TACE procedure and are associated with therapeutic failure. Abstract : What's new? Transarterial chemoembolization (TACE) is recommended as the first line of treatment for intermediate‐stage hepatocellular carcinoma, but efficacy assessment methods need to be improved. This prospective study evaluates the clinical impact of a‐fetoprotein and circulating cell‐free and tumor DNA changes around the TACE procedure. The results suggest that circulating cell‐free and tumor DNA dynamics may represent a promising marker to help evaluate treatment strategies after a first TACE procedure. A significant peak release of circulating DNA markers was observed after TACE, with a circulating tumor DNA detection rate at Day 2 that was almost twice as high as that at baseline.